Case Report: Myopathy in Critically Ill COVID-19 Patients: A Consequence of Hyperinflammation? - Versace, Viviana; Sebastianelli, Luca; Ferrazzoli, Davide; Saltuari, Leopold; Kofler, Markus; Löscher, Wolfgang; Uncini, Antonino (Frontiers in Neurology, 2021)
Introduction: COVID-19-associated muscular complications may comprise myalgia, weakness, wasting, and rhabdomyolysis. Skeletal muscle damage in COVID-19 may be due to direct infection by the virus SARS-CoV-2 through interaction with the ACE2 receptor, systemic hyper-inflammatory state with cytokine release and homeostatic perturbation, an autoimmune process, or myotoxic drugs. Disclosing the cause of weakness in an individual patient is therefore difficult. Case Description: We report two patients, who survived typical COVID-19 pneumonia requiring intensive care treatment and who developed early on myalgia and severe proximal weakness in all four limbs. Laboratory exams revealed elevated serum creatine kinase and markedly increased C-reactive protein and interleukin 6, concurring with a systemic inflammatory response. On admission in neurorehabilitation (4 and 7 weeks after COVID-19 onset, respectively), the patients presented with proximal flaccid tetraparesis and limb-girdle muscle atrophy. Motor nerve conduction studies showed decreased amplitude and prolonged duration of compound muscle action potentials (CMAPs) with normal distal motor latencies and normal conduction velocities in median and ulnar nerves. Needle electromyography in proximal muscles revealed spontaneous activity in one and myopathic changes in both patients. Discussion: Clinical, laboratory, and electrodiagnostic findings in these patients were unequivocally consistent with myopathy. Interestingly, increased distal CMAP duration has been described in patients with critical illness myopathy (CIM) and reflects slow muscle fiber conduction velocity due to membrane hypo-excitability, possibly induced by inflammatory cytokines. By analogy with CIM, the pathogenesis of COVID-19-related myopathy might also depend on hyperinflammation and metabolic pathways that may affect muscles in a pathophysiological continuum from hypo-excitability to necrosis.